Factors Influencing Hyperuricemia: Evidence from Sukoharjo, Central Java, Indonesia - Wulandari, Dewi (Indonesian Journal of Medicine, 2019)
Background: Hyperuricemia is an elevated serum uric acid level. It causes urate deposits in the joints, tendons, and other tissues as physiological prerequisites for gout. Hyperuricemia is also related to the existence and severity of several comorbidities, such as hypertension, cardiovascular disease, diabetes, and metabolic syndrome. The result of basic health research in 2018 showed that the prevalence of joint disease in Indonesia based on a doctor's diagnosis was 7.3%. The highest prevalence was in Aceh (13.3%). The lowest prevalence was in West Sulawesi (3.2%). This study aimed to examine factors associated with hyperuricemia.Subjects and Method: This was an analytical observational study with a case control design. The study was conducted in Sukoharjo, Central Java, from January to April, 2018. A sample of 90 study subjects was selected by consecutive sampling. The dependent variable was hyperuricemia. The independent variables were age, sex, stress, purine-rich foods intake, and family history of gout. Stress was measured by depression, anxiety, and stress scale (DASS 42). The other variables were collected by questionnaire. The data were analyzed by a multiple logistic regression.Results: Older age (OR= 13.80; 95% CI= 3.36 to 56.66; p<0.001), female (OR= 1.94; 95% CI= 3.36 to 7.62; p= 0.345), purine-rich foods intake (OR= 5.01; 95% CI= 1.48 to 16.97; p= 0.010), and stress (OR= 6.14; 95% CI= 1.83 to 20.60; p= 0.003) increased the risk of hyperuricemia. Family history of gout (OR= 1.47; 95% CI= 0.43 to 5.04; p= 0.537) increased the risk of hyperuricemia, but it was statistically non-significant.Conclusion: Age, female, purine-rich foods intake, and stress increase the risk of hyperuricemia. Family history of gout increases the risk of hyperuricemia, but it was statistically non-significant. Keywords: hyperuricemia, purine-rich food, stressCorrespondence: Dewi Wulandari. School of Health Sciences Mitra Husada. Jl. Ahmad Yani 167, Gapura Papahan Indah, Papahan, Tasikmadu, Karanganyar 57722, Central Java. Email: mujahidfiisabiilillah@gmail.com. Mobile: 089695098491.Indonesian Journal of Medicine (2019), 4(4): 321-328 https://doi.org/10.26911/theijmed.2019.04.04.04